Nasalence Value for Rainbow Passage: Normative Data for Non-Native Speakers - Sangeetha M; Pushpavathi M. (Journal of All India Institute of Speech and Hearing, 1970)
The development of normal speech is the most important goals of a clinician. The speech disorders associated with cleft lip and palate include abnormal consonant production, abnormal nasality, nasal air emission, nasal turbulence, and unintelligible speech. Nasality is measured subjectively and objectively. The ratio of acoustic energy output from the oral and nasal cavities of the speaker is called “Nasalence”. Most normative data available for assessing resonance through instrumentation have been on English speaking population. The nasalance is influenced by several parameters such as age, language, dialect, speech stimuli and gender. Hence the present study investigated nasalence values in Non- native English speakers using RAINBOW passage. Mean nasalence scores were obtained from 45 normal males and 70 normal females. The results indicated higher nasalence percent and variability in females compared to males. The mean nasalence value was 31.39 for females and 27.93 for males. A comparison of the nasalence values for Rainbow passage across various studies reveal significant differences except Hutchinson etal. (1978). this difference is due to the difference acrosssubjects, age and the instrumentation.